The Role of Alvarado and Pediatric Appendicitis Score in Acute Appendicitis in Children - Yelda Türkmenoğlu (Journal of Pediatric Research, 2020)

(untitled)
Aim:Acute appendicitis (AA) is the condition that most commonly requires a surgical procedure in children presenting to the emergency department with acute abdominal pain. Alvarado and Pediatric Appendicitis scores (PAS) are the most widely used scoring systems in the diagnosis of AA in children. This study aims to evaluate the effectiveness of Alvarado and PAS scores in the diagnosis of AA in children.Materials and Methods:One hundred and two patients aged 3-17 years, who were admitted to the pediatric emergency department with acute abdominal pain and had a clinical suspicion of AA were included in this retrospective study. The demographic characteristics, laboratory and radiological findings, and Alvarado and PAS scores were obtained from the records of the patients, retrospectively. According to the results of pathology, n=48 patients for the AA group and n=54 patients for the non-AA group were identified. The AA and non-AA groups were compared in terms of PAS and Alvarado scores.Results:The mean age of the 102 patients was 9.38±3.90 years, and 62 (60.85%) of them were male. The median PAS score was 7.79±1.2 and 5.52±1.34, and the median Alvarado score was 7.98±1.14 and 5.89±1.53 in the AA and N-AA groups, respectively (p<0.001; p<0.001). For the PAS, the cut-off score was >7 with a sensitivity of 66.7%, a specificity of 94.4%, a positive predictive value (PPV) of 91.4%, and a negative predictive value (NPV) of 76.1% (p<0.001). For the Alvarado score, the cut-off was also >7, with a sensitivity of 77.1%, a specificity of 85.2%, PPV of 82.2%, and NPV of 80.7% (p<0.001).Conclusion:Although both PAS and Alvarado scores provide useful diagnostic information in patients suspected of AA, neither of them is enough to diagnose AA alone.